Modern Breeding Approaches for durable Resistance against the parasitic Plant Striga - Runo, Steven (Afrika Focus, 2019)
Crop losses caused by parasitic plants of the genus Striga pose a great danger to the livelihoods of millions of smallholder farmers in Africa. The parasite attaches to host crops and siphons nutrients leading to severe retardation and crop death. Controlling Striga is difficult because of the parasite’s ability to produce large amounts of seeds that can remain dormant in the soil for decades – only germinating in response to chemical cues (strigolactones) from the host. In recent years, breeding crops for host-based resistance has been prioritized. However, such programs have not taken into account Striga’s ability to overcome host resistance. As a result, introduced resistance fails because of increased Striga virulence (infection severity). This article reviews technologies for a new paradigm in Striga resistance breeding that incorporates host resistance breeding with well-informed knowledge of parasite resistance in order to ensure durability of resistance. KEY WORDS: STRIGA, HOST BASED RESISTANCE, GENOME WIDE ASSOCIATION MAPPING, RNA SEQUENCING